SURVEI TINGKAT KETERBATASAN AKSES TEKNOLOGI DAN MINAT BELAJAR SISWA PADA PEMBELAJARAN PPKN DI SEKOLAH DASAR - Fitriana, Desi; Chan, Faizal; Alirmansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the condition of limited access to technology and the level of students' interest in learning Civics Education (PPKn) in Elementary School. This research used a quantitative approach with a descriptive survey method. The research subjects were 49 fourth, fifth, and sixth grade students selected through purposive sampling. Data were collected using a Guttman scale questionnaire validated through expert judgment. The data were analyzed using descriptive statistics by calculating the mean and achievement percentage. The results showed that the level of limited technology access was in the